HUBUNGAN INTENSITAS SOSIALISASI PENCEGAHAN HIV/AIDS DAN PERSEPSI TENTANG KREDIBILITAS KONSELOR TERHADAP SIKAP MENDUKUNG IBU RUMAH TANGGA MENGENAI PENCEGAHAN HIV/AIDS DI KABUPATEN BANJARNEGARA - Ainani Shifa Izazi; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
HIV / AIDS is one of the infectious diseases whose sufferers continue to increase year by year, including in Banjarnegara Regency. The increase in Banjarnegara Regency alone reached 85% until 2018 and housewives were the second highest number of cases. Therefore, prevention measure is necessary so that the infection is not widespread. This study aimed to examine whether the intensity of socialization and the perception of counselor credibility could influence the attitude of housewives in supporting the prevention of HIV / AIDS. Some of the theories used for reference in this study include information-integration theory, communication competency theory, and Source of credibility theory. The type of research was explanatory, which is the type of research that explains the causal relationship between variables studied by conducting hypothesis testing using the coefficient formula and Kendall Tau-B. It was obtained that there was no relationship between the intensity of socialization and the attitude of housewives to HIV / AIDS prevention. This result indicated that the socialization performed only provided little knowledge or only made little impact on cognition and did not arrive at a decision or attitude. However, perception of the counselor credibility and the attitude of housewives had a very significant and strong relationship. This result implied that respondents trusted HIV counselors strongly as people who were truly credible in handling, preventing HIV/AIDS in in Banjarnegara District.